Preferred Conformers and Photochemical (λ > 200 nm) Reactivity of Serine and 3,3-Dideutero-Serine In the Neutral Form - Jarmelo, S. (2005)
A systematic investigation of the conformational potential energy surface of neutral serine [HOCH2CHNH2COOH] and 3,3-dideutero-serine [HOCD2CHNH2COOH] was undertaken, revealing the existence of 61 different minima. The structures and vibrational spectra of the most stable conformers, which were estimated to have relative energies within 7 kJ mol-1 and account for ca. 93% of the total conformational population at room temperature, were calculated at both the MP2 and DFT/BLYP levels of theory with the 6-311++G(d,p) basis-set and used to interpret the spectroscopic data obtained for the compounds isolated in low-temperature inert matrixes. The assignment of the main spectral infrared features observed in the range 4000−400 cm-1 to the most stable conformers of serine was undertaken. In addition, UV irradiation (λ > 200 nm) of the matrix-isolated compounds was also performed, leading to decarboxylation, which was found to be strongly dependent on the conformation assumed by the reactant molecule.